2020
DOI: 10.1155/2020/9843486
|View full text |Cite
|
Sign up to set email alerts
|

Using Traditional Chinese Medicine to Treat Hepatocellular Carcinoma by Targeting Tumor Immunity

Abstract: As the leading cause of cancer-related death, hepatocellular carcinoma (HCC) threatens human health and limited treatments are available to cure the disease efficiently and effectively. The particularly immunotolerant environment of the liver lowers the efficacy of current therapies in patients with advanced HCC. Traditional Chinese medicine (TCM) is gathering increasing interest due to the immunoregulatory properties of certain compounds. In advanced HCC, TCM can restore immunosurveillance to promote antitumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 115 publications
(129 reference statements)
1
16
0
Order By: Relevance
“…Previous studies indicated that cancer patients with TCM deficiency syndrome have lower immune function and shorter survival time, while cancer patients with excess syndrome have better immune function and longer survival time, which supports the finding of our study [ 9 ]. Also, TCM can promote the antitumor effect by restoring immunosurveillance, including upregulating immunostimulatory factors and downregulating immunosuppressive factors [ 25 ]. Besides, compared with conventional therapies of cancer-associated symptoms, the incidence of related adverse events was not increased in the TCM groups [ 26 ], and a prospective cohort study showed that TCM prescriptions were safe and tolerable to most cancer patients [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that cancer patients with TCM deficiency syndrome have lower immune function and shorter survival time, while cancer patients with excess syndrome have better immune function and longer survival time, which supports the finding of our study [ 9 ]. Also, TCM can promote the antitumor effect by restoring immunosurveillance, including upregulating immunostimulatory factors and downregulating immunosuppressive factors [ 25 ]. Besides, compared with conventional therapies of cancer-associated symptoms, the incidence of related adverse events was not increased in the TCM groups [ 26 ], and a prospective cohort study showed that TCM prescriptions were safe and tolerable to most cancer patients [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis showed that TCM treatment improves the immune response for unresectable HCC after TACE treatment ( Meng et al, 2011 ). TCM is gathering increasing interest due to the immunoregulatory properties of certain compounds which can restore immunosurveillance in HCC to promote anti-tumor effects in several pathways, including the upregulation of immunostimulatory factors and the downregulation of immunosuppressive factors ( Jia and Wang, 2020 ). Several clinical studies have demonstrated that the utility of TCM can reduce adverse events after the TACE treatment of HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis showed Traditional Chinese Medicine (TCM) improves immune response for unresectable hepatocellular carcinoma (UHCC) after transcatheter arterial chemoembolization (TACE) 21 . TCM is gathering increasing interest due to the immunoregulatory properties of certain compounds, it can restore immunosurveillance in HCC to promote anti-tumor effects in several ways, including the upregulation of immunostimulatory factors and the downregulation of immunosuppressive factors 22 . And also clinical studies have demonstrated the utility of TCM in relieving adverse events after TACE, Tang et al found the chinese medicine Jianpi Ligan decoction (JLD) was effective for reduction of side effects and improvement of long-term survival for patients with unresectable HCC treated by TACE 23 .…”
Section: Discussionmentioning
confidence: 99%